A portal based knowledge management solution for an editorial department - Mohamed, Aida (2005)
The core business knowledge in an editorial department mainly comes from individuals that are involved in the publishing processes. The exclusiveness of knowledge can help an individual to get a better position or better role in the department. Because of that, these individuals tend not to share what they know in order to protect their so called personal asset. Up to date, there are still no available tools or platform that has been developed to enable knowledge sharing in the respective industry. Therefore, this study is conducted to identify and manage the knowledge exists. A Knowledge Audit was being conducted in one of the biggest publishing organization to better understand the current situation of knowledge flows, ownership and sharing methods. A test prototype of a knowledge portal was developed as the tool for managing the organizational knowledge and as a medium to transfer the knowledge ownership from an individual to organization’s intellectual assets. The portal has the capability to provide knowledge sharing, knowledge references and most importantly the person that has the knowledge is now being acknowledged. The portal was developed using Macromedia DreamWeaver MX as the editor and Active Server Pages (ASP) as the programming script. The system was designed using the Unified Modeling Language (UML) form and the methodology to develop the system was based on the APQC’s roadmap. Few management strategies to institutionalize knowledge management were proposed in the final stage of the research phase. The strategies that have been laid out can be used as guidance for achieving a more effective knowledge management environment in a publishing organization.